An assessment of the literature on cause-related marketing: implications for international competitiveness and marketing research - Vrontis, Demetris; Christofi, Michael; Katsikeas, Constantine S. (My University, 2020)
Purpose: A substantial, albeit scattered, body of research evidence is accumulating in the cause-related marketing (CRM) research stream. Thus, there is a need of a systematic overview of extant literature to map and holistically understand the CRM domain. Design/methodology/approach: To address this issue and make progress in this important area, the authors systematically review and critically examine the state of academic research on CRM. Findings: Based on a systematic review of 105 journal articles published over the past 30 years, the results reveal that CRM research is a vibrant and rapidly growing domain in the broader marketing field. This assessment exercise also shows that the current state of knowledge about CRM is characterized by persisting knowledge gaps, conflicting empirical results, theoretical inconsistencies, as well as by the absence of international marketing research on the CRM domain. Originality/value: Therefore, the authors critically evaluate the extant CRM research with the aim of increasing its coherence, quality, scope, impact and international dimension. Based on this evaluation, the authors develop an ambitious research agenda that addresses a number of promising research paths embracing different international perspectives. Finally, the authors discuss the contributions to the literature and the implications for both academics and practitioners.
Keywords: Cause-related marketing; Critical appraisal; International marketing research; Research agenda; Systematic review